Menopause and hormone replacement therapy (Medical Journal of Indonesia, 2001)
The global population in the 21st century has reached 6.2 billion people, by the year 2025 it is to be around 8.3-8.5 billion, and will increase further. Elderly people are expected to grow rapidly than other groups. The fastest increase in the elderly population will take place in Asia. Life expectancy is increasing steadily throughout developed and developing countries. For many menopausal women, increased life expectancy will accompanied by many health problems. The consequences of estrogen deficiency are the menopausal symptoms. The treatment of menopause related complaints and diseases became an important socioeconomic and medical issue. Long term symptoms, such as the increase in osteoporosis fractures, cardio and cerebrovascular disesses and dementia, created a large financial burden on individuals and society. All these health problems can be lreated or prevented by hormone replacement therapy (HRT). Natural HRT is usually prefened. Synthetic estrogen in oral contraceptives (oc) are not recommended for HRT. Many contra-indications for oc, but now it is widely usedfor HRT. The main reasons for discontinuing HRT are unwanted bleeding, fear of cancer, and negative side effects. Until now there are sill debates about the rebrtonship between HRT and the incidence of breast cancer. Many data showed that there were no clear relationship between the use of HRT and breast cancer. Therefore, nwny experts advocate the use of HRTfrom the first sign of climacteric complaints until death. (Med J Indones 2001;10: 242-51)